Drought response of the boreal forest carbon sink is driven by understorey–tree composition - Martínez-García, Eduardo; Nilsson, Mats B.; Laudon, Hjalmar; Lundmark, Tomas; Fransson, Johan E. S.; Wallerman, Jörgen; Peichl, Matthias (Springer Nature, 2024)
The boreal forest is an important global carbon sink, but its response to drought remains uncertain. Here, we compiled biometric- and chamber-based flux data from 50 boreal forest stands to assess the impact of the 2018 European summer drought on net ecosystem production (NEP) across a 68 km2 managed landscape in northern Sweden. Our results reveal a non-uniform reduction in NEP (on average by 80 ± 16 g C m−2 yr−1 or 57 ± 13%) across the landscape, which was greatest in young stands of 20–50 years (95 ± 39 g C m−2 yr−1), but gradually decreased towards older stands (54 ± 57 g C m−2 yr−1). This pattern was attributed to the higher sensitivity of forest-floor understorey to drought and its decreasing contribution to production relative to trees during stand development. This suggests that an age-dependent shift in understorey–tree composition with increasing stand age drives the drought response of the boreal forest NEP. Thus, our study advocates the need for partitioning ecosystem responses to improve empirical and modelling assessments of carbon cycle–climate feedbacks in boreal forests. It further implies that the forest age structure may strongly determine the carbon sink response to the projected increase in drought events across the managed boreal landscape.